Case report: The cardio-facio-cutaneous syndrome due to a novel germline mutation in MAP2K1: A multifaceted disease with immunodeficiency and short stature - Szczawińska-Popłonyk, Aleksandra; Popłonyk, Natalia; Niedziela, Marek; Sowińska-Seidler, Anna; Sztromwasser, Paweł; Jamsheer, Aleksander; Obara-Moszyńska, Monika (Frontiers in Pediatrics, 2022)
Cardio-facio-cutaneous syndrome (CFCS) belongs to the group of RASopathies, clinical disorders defined by disruptions in the RAS/MAPK signaling pathway. It is caused by heterozygous gain-of-function germline mutations in genes encoding protein kinases: BRAF, MAP2K1 (MEK1), MAP2K2 (MEK2), and in the GTPase-encoding gene KRAS. CFCS is characterized by craniofacial dysmorphic features, congenital heart defects, severe malnutrition, proportionate short stature, anomalies within the structure of skin and hair, and psychomotor disability. The pathophysiology of growth impairment is multifactorial with feeding difficulties, growth hormone deficiency, and insensitivity. Immunodeficiency has not been hitherto reported as an integral part of CFCS yet an increased activation of the RAS/MAPK signaling pathway may contribute to explaining the causal relationship between RASopathy and the dysfunctions within the B and T lymph cell compartments resulting in a deficiency in T cell costimulation and B cell maturation with impaired class switch recombination, somatic hypermutation, and high-affinity antibody production. We report on a boy born prematurely at 32 WGA, with the perinatal period complicated by pneumonia, respiratory distress syndrome, and valvular pulmonary stenosis. The boy suffered from recurrent pneumonia, obstructive bronchitis, sepsis, urinary tract infection, and recurrent fevers. He presented with severe hypotrophy, psychomotor disability, short stature, craniofacial dysmorphism, dental hypoplasia, sparse hair, and cryptorchidism. Whole genome sequencing showed a novel heterozygous pathogenic germline missense variant: c.364A>G; p.Asn122Asp in the MAP2K1 gene, supporting the diagnosis of CFCS . The immunological workup revealed hypogammaglobulinemia, IgG subclass, and specific antibody deficiency accompanied by decreased numbers of T helper cells and naive and memory B cells. Replacement immunoglobulin therapy with timely antibiotic prophylaxis were instituted. At the age of six years, growth hormone deficiency was diagnosed and the rGH therapy was started. The ever-increasing progress in genetic studies contributes to establishing the definitive CFCS diagnosis and sheds the light on the interrelated genotype-phenotype heterogeneity of RASopathies. Herein, we add new phenotypic features of predominating humoral immunodeficiency to the symptomatology of CFCS with a novel mutation in MAP2K1. While CFCS is a multifaceted disease, increased pediatricians’ awareness is needed to prevent the delay in diagnostics and therapeutic interventions.